ANALISIS KAPASITAS BANDARA HALIM PERDANAKUSUMA SEBAGAI BANDARA KOMERSIL - Arief Hadi Wibowo; Risky Duta Ramadhan; Bambang Riyanto; Epf. Eko Yulipriyono (Jurnal Karya Teknik Sipil, 2015)
Halim Perdanakusuma airport is one of military airport which placed in DKI Jakarta. Since Soekarno-Hatta airport has been crowded on January 10th 2014, Halim Perdanakusuma airport has became Commercial airport formally and military airport (The office of Indonesian airport) too. It is based on Soekarno-Hatta airport’s capacity that not able to accommodate airplane movement, increasing runway and developing airport’s capacity. Therefore, needed an analysis of Halim Perdanakusuma ability in air side which is able to accommodate military airplane movement and commercial airplane based on existing. The methodology sequence that used to write this thesis is contain data collecting by field observation to getting primary data air traffic and secondary data from airport management in the form of flight schedule data, the existing condition of the airport that processed with a mathematical perspective. The calculating by modeling methods; arrival flight, take off and mixed operation. Based on current condition of existing, Halim Perdanakusuma airport has 1 runway which 3000 meters long 45 meters width, 5 taxiways for commercial and 3 for military, 1 main-apron on 88.787,5 m2 areas which able to accommodate 14 airplanes type boeing 737-900 and 3-sized Cessna airplane. According to the calculation, Halim’s air traffic in mixed operation was 15 ops/hour, Halim needed 9 gates to reach it’s maximum operating according to those traffic, needed 49.059,5 m2 areas of apron, with taxiway capacities 70-90 ops/hour. Based on those result, Halim Perdanakusuma airport is very maximum operating with just the management adjustments, because all its elements in tolerant and it can fulfill the minimum standards in all aspects.